ANALYSIS OF ENGLISH LANGUAGE NEEDS IN NURSING STUDENTS OF MUHAMMADIYAH PONOROGO UNIVERSITY - Riwasanti, Marsely Forma; Maghfiroh, Ana; Mustikawati, Diyah Atiek (IKIP Siliwangi, 2021)
English in universities is taught as a general course in non-English majors, as in the case at the Nursing Department, Muhammadiyah Ponorogo University. Ideally, the content presented should be adjusted to the department, which is referred to as ESP (English for Specific Purpose). Perceptions from several parties are needed to find out how important English is for a career as a nurse and the right material according to their needs. This research aimed to analyze the students’ needs on English for Specific Purposes materials, particularly at the Nursing department, University of Muhammadiyah Ponorogo. The researcher used questionnaire as the research instrument. The subject were the sixth semester students of Muhammadiyah Ponorogo Nursing Academy in the academic year 2018/2019 with the total number of 90 students in three classes. The researchers decided to take only 20% of the total students, namely 15 students for all classes. The results of this study indicate that in general, respondents believe that English is very important to be taught in the Nursing Department. English is taught as a general course, but students expect material relevant to their assignments in the workplace. Teacher of ESP English courses or interested individuals can Keywords: ESP, English Subject, Needs Analysis, Learners’ Needs